2016
DOI: 10.1016/j.jeurceramsoc.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of defects in microwave and conventionally synthesized LaCoO3 perovskite

Abstract: Citation for published item:rdoEqonjlD tF nd quti¡ errezEeijsD tF nd rerrero ensorreguiD sF nd wor¡ nD iF nd erryD sF nd hmidtD F @PHITA 9he role of defets in mirowve nd onventionlly synthesized vgoyQ perovskiteF9D tournl of the iuropen germi oietyFD QT @SAF ppF IIWUEIPHTF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…These Co 2+ cations constitute magnetic impurities, which have been shown recently to act as nucleation centers for the formation of higher spin states across the spin-state transition [11]. However, the weight loss measured here indicated that possible oxygen vacancies in all synthesized powder samples would exhibit a small concentration below the resolution limit of the TGA balance.…”
Section: Oxygen Contentmentioning
confidence: 52%
See 4 more Smart Citations
“…These Co 2+ cations constitute magnetic impurities, which have been shown recently to act as nucleation centers for the formation of higher spin states across the spin-state transition [11]. However, the weight loss measured here indicated that possible oxygen vacancies in all synthesized powder samples would exhibit a small concentration below the resolution limit of the TGA balance.…”
Section: Oxygen Contentmentioning
confidence: 52%
“…The Co 3+ spin states may be (a) low-spin (LS) (t2g 6 eg 0 ), (b) intermediate-spin (IS) (t2g 5 eg 1 ), or (c) high-spin (HS) (t2g 4 eg 2 ) [10][11][12]. The competition between different spin states has caused large controversy in the literature previously [10,[12][13][14][15][16][17][18][19], but in most studies only the case of LaCoO3 has been considered.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations